2014
DOI: 10.1101/003194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic tree shapes resolve disease transmission patterns

Abstract: A B S T R A C TBackground and Objectives: Whole-genome sequencing is becoming popular as a tool for understanding outbreaks of communicable diseases, with phylogenetic trees being used to identify individual transmission events or to characterize outbreak-level overall transmission dynamics. Existing methods to infer transmission dynamics from sequence data rely on well-characterized infectious periods, epidemiological and clinical metadata which may not always be available, and typically require computational… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In addition, they allow us to construct offspring distributions for different phases of the epidemic across different realizations and transmission tree structures [ 22 , 23 ] that might provide clues to the role of superspreaders [ 14 ], or other heterogeneities in the susceptibility and infectiousness of individuals (e.g., deceased patients and unsafe burial ceremony). Information on offspring distributions can also be used to help fit models to single outbreaks [ 24 ].…”
Section: Alternative Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they allow us to construct offspring distributions for different phases of the epidemic across different realizations and transmission tree structures [ 22 , 23 ] that might provide clues to the role of superspreaders [ 14 ], or other heterogeneities in the susceptibility and infectiousness of individuals (e.g., deceased patients and unsafe burial ceremony). Information on offspring distributions can also be used to help fit models to single outbreaks [ 24 ].…”
Section: Alternative Simulation Resultsmentioning
confidence: 99%
“…With the rapidly increasing power of genetic sequencing methodologies, transmission trees can be constructed for viral pathogens, such as EBOV [ 25 ], using genetic data [ 12 , 22 , 26 , 27 ]. Thus, despite being a very challenging problem, the key to fitting a stochastic process model to a single realization, represented by a particular outbreak, appears to be rooted in fitting the model to the associated offspring and phylogenetic tree distributions that emerge and that better characterize the actual process [ 23 , 24 ] than the much more variable case size or R 0 statistic. It has recently been reported that EBOV genomes were sequenced, using blood samples from 78 patients in Sierra Leone [ 25 ].…”
Section: Model Fitting Considerationsmentioning
confidence: 99%
“…These parameters capture two phenomena that have been widely used for phylogenetic studies. The parameter β ∈ [−2, ∞), as in the beta-splitting model (37), determines the degree of balance, an important tree attribute that car-ries information on underlying evolutionary or epidemiological processes, including speciation and extinction (38)(39)(40)(41), natural selection (42)(43)(44)(45), and infectious disease transmission (46)(47)(48). The other parameter α ∈ (−∞, ∞) regulates the relationship between clade family size and proximity to the root (clade sizeage relation), which is fundamental to understanding the effects of ecological, evolutionary, geographic, and other factors on biodiversity (7,(49)(50)(51)(52).…”
Section: Resultsmentioning
confidence: 99%
“…Other definitions for ladder length, maximum depth of a tree, maximum width and maximum width over maximum depth can be found in [17]. The implementation of phylogenetic tree simulation and computation of tree statistics were implemented in Python software, version 3.7.3.…”
Section: Methodsmentioning
confidence: 99%